Eosinophils are dispensable for the regulation of IgA and Th17 responses in Giardia muris infection. (23rd September 2020) - Yordanova, Ivet A.; Lamatsch, Martin; Kühl, Anja A.; Hartmann, Susanne; Rausch, Sebastian
Abstract: Aims: IgA and Th17 responses are pivotal for the control of Giardia infections. Eosinophils support IgA class switching, the survival of intestinal IgA + plasma cells at steady state and can control Th17 activity in the small intestine. To see whether eosinophils regulate adaptive immune responses during giardiasis, we investigated Giardia muris infections in wild‐type BALB/c and eosinophil‐deficient ∆dblGATA‐1 mice. Methods and results: Infected ∆dblGATA‐1 mice did not differ markedly in parasite control from wild‐type mice. Confirming previous studies, naive ∆dblGATA‐1 mice displayed diminished IgA + B cell frequencies in Peyer's patches. However, IgA class switching and intestinal IgA secretion in response to G muris infection were comparable in wild‐type BALB/c and ∆dblGATA‐1 mice. Both strains displayed similarly low intestinal Th17 responses, accompanied by a mild expansion of type 3 innate lymphoid cells (ILC3). Conclusions: Contrasting previous reports on overt small intestinal Th17 activity in eosinophil‐deficient mice, IL‐17A production is kept in check in the absence of eosinophils during Giardia infection. Suboptimal homeostatic IgA responses in the absence of eosinophils are transiently fostered in infected mice and the maintenance of IgA + plasma cells appears to be restored during persisting Giardia infection.